Economia Popular Solidária: Os Processos Formativos Populares e a Construção de uma Nova Cultura do Trabalho - Laurencio Mendes da Silva (2007)
This study aims to analyze human education in the process of work and the implications of education practices associated to the self-management productive process in the solidary popular economy, seeking to understand the way in which they contribute to the construction, dissemination and strenghthening of a new work culture. The subjects of this research were the workers of self-management popular groups aided by Pastoral Operária de Minas Gerais 2 (Labor Pastoral of the State of Minas Gerais), distributed by different regions in the State and most of them women. Data were collected through individual and group interviews, participant observation and document analysis. The aspects focused included a set of activities present in the forms of work management, workers political and social organization, such as: plannings, projects, meetings and the dinamism itself in the productive process and social relations, types of workers involvement in the group and articulations networks. Aiming to broaden the understanding of the connection between education and work, we start from the assumption that work is an education principle, taking into consideration Lukács, Marx and Gramscis theoretical contributions. These authors conceive work in its double dimension (ontological dimension and historical dimension), as a source of production and assumption of knowledge and attainments thus an education principle. The data analysis enabled us to get to some critical considerations and conclusions over the reality of the subjects of study. Consequently, we noticed that these new ways of work organization lead to their iniciative practices and education proposals that contribute to a certain extent to the construction of a new culture, constituted by new relations of work, that reflect on the workers profiles, their world visions, their way of intefering in the reality of their own work and their new way of organization as a category. Besides, it has been observed that the present work market demands tend to articulate new practices and new discourses, that is, new survival strategies in changing world. This movement shows us the origin of new values, new workers postures before society, work world, its requirements and demands.